ENCICLOPEDIA DE MEXICO - Alvarez, José Rogelio (dirección) (1977)
CONTENIDO: V. 4 FAMILIA-FUTBOL. -- V. 5 GABINETES-GUADALAJARA. -- V. 6 GUADALUPE-HONGOS. -- V. 7 HONOR-LASSAGA. -- V.8 LATAPI-MEXICO. -- V. 9 MEZA-OROZCO. -- V. 10 ORQUIDEAS-QUETZAL. -- V. 11 QUETZALCOATL-TAMAULIPAS. -- V. 12 TAMAYO-ZURITA